An evaluation of the genus Amphidinium (Dinophyceae) combining evidence from morphology, phylogenetics, and toxin production, with the introduction of six novel species - Karafas, Sarah; Sing, Tung Teng; Chui, Pin Leaw; Alves-de-Souza, Catharina (Elsevier Ltd., 2017)
The genus Amphidinium is an important group of athecated dinoflagellates because of its high abundance in marine habitats, its member’s ability to live in a variety of environmental conditions and ability to produce toxins. Furthermore, the genus is of particular interest in the biotechnology field for its potential in the pharmaceutical arena. Taxonomically the there is a history of complication and confusion over the proper identities and placements of Amphidinium species due to high genetic variability coupled with high morphological conservation. Thirteen years has passed since the most recent review of the group, and while many issues were resolved, some remain. The present study used microscopy, phylogenetics of the 28S region of rDNA, secondary structure of the ITS2 region of rDNA, compensatory base change data, and cytotoxicity data from Amphidinium strains collected world-wide to elucidate remaining confusion. This holistic approach using multiple lines of evidence resulted in a more comprehensive understanding of the morphological, ecological, and genetic characteristics that are attributed to organisms belonging to Amphidinium, including six novel species: A. fijiensis, A. magnum, A. paucianulatum, A. pseudomassartii, A. theodori, and A. tomasii.